An exploration of teachers' perspectives on computational thinking in mathematics learning - I Gusti Nyoman Yudi Hartawan; I Gusti Ngurah Pujawan; Nyoman Arda Wibawa (Indonesian Journal of Educational Development (IJED), 2026)
The integration of Computational Thinking (CT) into mathematics learning has become a key demand in 21st-century education, as it plays an important role in developing logical, creative, and systematic thinking skills. However, in the context of Indonesian education, implementing CT still faces various challenges, particularly regarding teachers’ understanding and readiness to integrate it into the learning process. This study aims to explore teachers’ perspectives on CT-based mathematics learning, including their understanding, perceived relevance, readiness, and the challenges they face in its implementation at the junior high school level. This study offers a novel contribution by explicitly distinguishing between teachers’ conceptual understanding of CT and their pedagogical readiness to implement CT in mathematics learning, a gap that has been insufficiently explored in previous studies. The study employed a qualitative approach with an exploratory design. The research population consisted of junior high school mathematics teachers in Singaraja City, Indonesia. Eight teachers were selected as research participants using purposive sampling based on criteria such as teaching experience, involvement in CT-related or technology-based learning, and willingness to participate in the study. Data were collected through semi-structured interviews, classroom observations, and analysis of learning documents, then analyzed inductively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the teachers’ perspectives on CT-based mathematics learning are conceptually positive but still limited in practice. CT is considered relevant and potentially effective in strengthening mathematical thinking skills; however, its implementation requires systematic support. Based on these findings, the study recommends providing continuous, practice-oriented professional development programs for teachers, developing CT-based mathematics teaching resources, and stronger policy support to facilitate the effective integration of CT into junior high school mathematics learning. The study's implications highlight the importance of strategies to strengthen teachers’ capacity.